From 5G to 6G: India's push for next-generation networks - Harjani, Manoj (2023)
India’s vision statement for 6G lays out an advanced plan for the country to implement the next generation of communications networks by 2030. However, having experienced a delayed 5G rollout and needing more domestic capabilities to facilitate indigenous technology development, India’s 6G ambitions require further evaluation. To ensure an optimal 6G rollout, India should aim to balance technical, commercial and national security concerns through a risk-based approach.